El método de análisis insumo-producción - Szychowski, Mario Luis (1966)
This work is a synthesis of the model or method of analysis viewed according to the new contributions which have appeared since Leontief's original publication. The author emphasizes the difference between the table and the model itself of input-output, the two integrating parts of the model. Regarding the former, he points out its definitions and characteristics, the duality of its contents, the relation of its results with the concept of gross national product and some special problems concerning its construction. Referring to the model itself he explains its operational mechanism and its solution through the matrix theory.